2022
DOI: 10.1186/s12913-022-07753-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Covid-19 pandemic on primary health care utilization: an experience from Iran

Abstract: Background The Covid-19 pandemic affected the performance of Primary Health Care (PHC) worldwide. This study was performed to investigate the impact of the Covid-19 pandemic on the utilization of PHC in Iran. Method A before and after study conducted between 2019 and 2021. 56 medical science universities across the country were studied. The data extracted from Electronic Health Record (EHR) is entitled “SIB”. Three major indicators included a weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…The COVID - 19 pandemic and the restrictions placed as part of controlling the pandemic affected the PHC service delivery globally [ 53 , 54 ] as in Kerala’s newly introduced FHC program. However, insofar as the FHC program itself was built on a strong edifice of reforms, backed by community participation and political will, the state had some early success in managing the pandemic [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID - 19 pandemic and the restrictions placed as part of controlling the pandemic affected the PHC service delivery globally [ 53 , 54 ] as in Kerala’s newly introduced FHC program. However, insofar as the FHC program itself was built on a strong edifice of reforms, backed by community participation and political will, the state had some early success in managing the pandemic [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have established a clear relationship between burnout and the bureaucratic burden, which reduces the time left for clinical activity [ 15 , 16 ]. The prioritization of COVID-19 care, both clinically and administratively, caused a displacement of care with respect to chronic diseases and the diagnosis of new health problems, the usual tasks of PHC in Spain and in other countries [ 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due, to the community phobia that limited patients’ consultations, the absenteeism of healthcare workers, and the closure of some healthcare facilities [ 14 ]. The literature has also demonstrated that there have been changes in the demand and offer of PHC services characterized by a decrease in in-person visits, a drop-in vaccination rate, and a rise in non-communicable diseases’ complications [ 15 , 16 , 17 ]. Second, PHC in Tunisia, as highlighted by the participants of the study, did not play an effective role in the management of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%